Konsep komunikasi pemasaran dalam mengenalkan produk home industri pondok pesantren Al Anwar - Anis Kurli; Zarnuji ,; Moh Baqir Ainun; Lily Elserisa (PUBLIC CORNER, 2023)
The concept of marketing communication in introducing products is needed in the marketing activities of home industry products at Putri Al Anwar Islamic Boarding School. The purpose of this research is to find out the concept of marketing communication in introducing home industry products at Putri Al Anwar Islamic Boarding School. The method used in this study is descriptive qualitative, the researcher tries to describe in detail the concept of marketing communications in marketing activities carried out by business actors. The results of research conducted on the concept of marketing communication in introducing home industry products at Putri Al Anwar Islamic Boarding School are determining the brand that will become the identity of the product produced, determining segmentation into small groups, determining target markets according to demographics, characteristics and consumer lifestyles, and positioning as branding that will always be remembered by consumers. Keywords: Concept, Marketing, Product